An overview of offshore wind energy resources in Europe under present and future climate. Issue 1 (15th July 2018) - deCastro, Maite; Costoya, Xurxo; Salvador, Santiago; Carvalho, David; Gómez‐Gesteira, Moncho; Sanz‐Larruga, Francisco Javier; Gimeno, Luis
Abstract: Long‐term sustainable development of European offshore wind energy requires knowledge of the best places for installing offshore wind farms. To achieve this, a good knowledge of wind resources is needed, as well as knowledge of international, European, and national regulations regarding conflict management, marine environment conservation, biodiversity protection, licensing processes, and support regimes. Such a multidisciplinary approach could help to identify areas where wind resources are abundant and where conflicts with other interests are scarce, support measures are greater, and licensing processes are streamlined. An overview of offshore wind power studies at present, and of their future projections for the 21st century, allows for determining the optimal European locations to install or maintain offshore wind farms. Only northern Europe, the northwest portion of the Iberian Peninsula, the Gulf of Lyon, the Strait of Gibraltar, and the northwest coast of Turkey show no change or increase in wind power, revealing these locations as the most suitable for installing and maintaining offshore wind farms in the future. The installation of wind farms is subject to restrictions established under international law, European law, and the domestic legal framework of each EU member state. Europe is moving toward streamlining of licensing procedures, reducing subsidies, and implementing auction systems. Abstract : Wind energy has become the second largest form of power generation capacity in the European Union because the cost has fallen at the same time that efficiency and availability have increased. We provide an overview of various studies of offshore wind and wind power in Europe at present and future projections for the 21st century to determine their suitability for characterizing present and future offshore wind energy resources.